PENGARUH RELATIONSHIP QUALITY DAN INFORMATION SHARING TERHADAP SUPPLIER PERFORMANCE DI PT XYZ - Yohan Gunawan; Radityo Fajar Arianto (Transpublika Publisher, 2024)
This study aims to analyze the influence of relationship quality and information sharing on supplier performance at PT XYZ. The study examines eight hypotheses, including the impact of trust, commitment, satisfaction with the organization, satisfaction with pricing, satisfaction with communication, information sharing on supplier loyalty, supplier communication, and supplier quality. The research method used is a survey with questionnaires distributed to 180 respondents from PT XYZ's supplier companies. Data analysis was conducted using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method. The results show that commitment has a positive impact on information sharing. Satisfaction with the organization and satisfaction with pricing were also found to have a positive impact on information sharing. Information sharing significantly enhances supplier loyalty, supplier communication, and supplier quality. However, the influence of trust and satisfaction with communication on information sharing was not proven significant. These findings reinforce the importance of building high-quality relationships and effective information sharing in improving supplier performance. The managerial implications of this study include strategies to maintain and enhance high performance, resource optimization, simple monitoring, and focusing on improving high-interest, low-performance areas. This study also identifies several limitations and provides suggestions for future research.